DAYA TERIMA ROTI SOURDOUGH DENGAN ISIAN PASTA PURPLE SWEET POTATO - Anton Kuswendi, - (2023)
Sourdough bread is a type of bread that is naturally made using natural yeast or commonly called sourdough. Sourdough is a mixture of flour and water or often also called natural yeast which comes from natural ingredients without any additives, so this method does not require commercial yeast in making bread. This research was conducted to develop sourdough bread with purple sweet potato paste as a bread that has a high fiber content that is acceptable to the public. The research method used is true experimental with the stages of recipe analysis, product trial, QDA test, and acceptability test. The test results for sourdough bread products consist of two parts, namely starter and bread, so there are two standard recipes. In the standard recipe, there are two ingredients used for starter, namely flour (60%) and water (40%). Bread is made of five ingredients, namely wheat flour (53.6%), starter (20.5%), salt (0.63%), butter (3.15%), and water (22.08%). From this standard recipe, a new formula was obtained for sourdough bread filled with purple sweet potato paste. The best formula for a starter is wheat flour (50%) and water (50%). As for the filling, it is made from purple sweet potato (47.5%), water (25.3%), coconut milk (12.7%), salt (0.3%), and condensed milk (7.9%). As for sourdough bread, it is made from wheat flour (47.5%), sourdough starter (21.4%), salt (1%), butter (4%), and water (2.4%). Acceptability test results show that sourdough bread with purple sweet potato paste filling can be accepted as bread that has a high fiber content with a score percentage of 80%.